Analisis Efisiensi Persediaan Beras di Kota Kendari dengan Menggunakan Metode Economy Order Quantity - Rusyaid, Andi Muhammad; Taridala, Sitti Aida Adha; Limi, Muhammad Aswar (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This research aims to: (1) Knowing the flow of rice procurement BULOG Divre Sultra; (2) Analyze and describe the efficiency of rice supply in Kendari City using Economic Order Quantity (EOQ) method at BULOG Divre Sultra. The study was designed as a case study using primary data and secondary data, variables in this study include Total Inventory Cost, Ordering Cost, and Carrying Cost. Based on the research indicates that the flow of rice procurement done by BULOG begins from BULOG Center will ask Kadivre/Kasubdivre/Kakansilog to make rice procurement. After that, BULOG will negotiate with MKP and Satker. Subsequently, MKP and Task Force will send the rice to the warehouse under an approved contract. After receiving the rice, KDP will check the quality, then issue LHPK to MKP as a condition of payment request to Kadivre/Kasubdivre/Kakansilog. The efficiency of rice supply costs that can be done by BULOG when applying the EOQ method of Rp 31,455,951. The use of the EOQ method can be recommended as an alternative to rice stock control. However, it should be adjusted to the policies and conditions of the company, in this case, BULOG Divre Sultra.